2017
DOI: 10.1016/j.tcb.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding Chromosomes After Catastrophe: Emerging Mechanisms of Chromothripsis

Abstract: Cancer genome sequencing has identified chromothripsis, a complex class of structural genomic rearrangements involving the apparent shattering of an individual chromosome into tens to hundreds of fragments. An initial error during mitosis, producing either chromosome missegregation into a micronucleus or chromatin bridge interconnecting two daughter cells, can trigger the catastrophic pulverization of the spatially isolated chromosome. The resultant chromosomal fragments are re-ligated in random order by DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
166
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(177 citation statements)
references
References 81 publications
(136 reference statements)
3
166
0
2
Order By: Relevance
“…Altogether, this complex rearrangement fits with a chromothripsis‐like event both for the shattering of a large portion of an individual chromosome into many fragments (Ly & Cleveland, ) and for the presence of an insertional translocation associated with a small deletion of the receiving chromosome next to the insertion site, as recently reported (Gu et al, ; Kato et al, ). The reconstruction of maternal and proband's rearrangement by WGS clearly indicated that proband's imbalance was the result of a meiotic recombination (Figure ) involving chromosome 3 only and leaving chromosome 8 intact.…”
Section: Discussionsupporting
confidence: 80%
“…Altogether, this complex rearrangement fits with a chromothripsis‐like event both for the shattering of a large portion of an individual chromosome into many fragments (Ly & Cleveland, ) and for the presence of an insertional translocation associated with a small deletion of the receiving chromosome next to the insertion site, as recently reported (Gu et al, ; Kato et al, ). The reconstruction of maternal and proband's rearrangement by WGS clearly indicated that proband's imbalance was the result of a meiotic recombination (Figure ) involving chromosome 3 only and leaving chromosome 8 intact.…”
Section: Discussionsupporting
confidence: 80%
“…However, in RPE-1 cells, the effect of peripheral chromosomes on NE disruption was 180 partly masked because the large micronuclei from peripheral chromosomes in these cells are 181 subject to actin-dependent NE breakage, as can occur transiently on primary nuclei 14 recently reported to assemble with fenestrated ER sheets 31 that might less readily penetrate 201 dense bundles of spindle microtubules than vesicles or tubules, which we speculate could be the 202 main source of core membrane proteins. 203 6 Together, our findings demonstrate that altered NE assembly on lagging chromosomes is 204 not the consequence of a beneficial checkpoint delay, but rather a pathological outcome. 205…”
mentioning
confidence: 83%
“…Consequently, during normal cell division, instead of precise and continuous monitoring of 206 chromosome position, it appears that there is only loose coordination, with normal non-core NE 207 assembly being dependent on timely spindle microtubule disassembly. Loose coordination, 208 coupled with the irreversibility of NE assembly errors during mitotic exit, provides one explanation 209 of why chromothripsis is common, with frequencies recently reported to be as high as 65% in 210 some cancers 5,6 .…”
mentioning
confidence: 99%
“…Interestingly, we observed no evidence for any widespread mutagenesis across the chromosome. Since the formation of ProGly complexes is not expected to be restricted to plasmid sites, the possibility exists that mutagenesis related events that result in the elimination of sequences encoding the toxic multivalent ProGly protein, occur rapidly following plasmid transformation, thereby minimising chromosomal damage., or that replication and subsequent cell division are delayed A more extensive set of genome sequencing would be necessary to test this more thoroughly and may have some relevance to the emerging observations of catastrophic genome remodelling in the cancer related phenomenon of chromothripsis (Ly and Cleveland (2017).…”
Section: Discussionmentioning
confidence: 99%